IMPLEMENTASI PENDEKATAN LOK-R DALAM MENINGKATKAN LITERASI PESERTA DIDIK - Yusiana, Ulfa; Mualifah, Titin; Chasanah, Uswatun; Muzayanah, Muzayanah; Sukamto, Yuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The application of the learning model carried out in grade 8 (6) at SMPN 1 Nganjuk which must be adjusted to the times. Through an independent curriculum to implement literacy-based learning, namely: reading literacy, science, socio-culture, and numeracy. Observations made in class show low literacy of students, where teachers only apply the lecture method. So the learning model of Literacy, Orientation, Collaboration, Reflection (LOK-R) is suitable to be used to improve literacy culture at SMPN 1 Nganjuk, especially grade 8(6). This research uses descriptive quantitative methods The application of literacy using the LOK-R approach aims to improve literacy culture so that students are able to understand and relate learning material to real events that occur. The output of this activity is evidenced through the results of research which shows that a number of 61% of students are in the effective category.